Cruel, Convenient, and Intimate Publics - Ali Azhar; Megan Boler (Media Theory, 2023)
Lauren Berlant’s contributions chart innovative conceptual frameworks to help us understand how affect and emotion, desires and hopes traverse the public and private realms. However, rather surprisingly, Berlant’s work does not engage directly with explorations of digital culture and its effects, nor has it been used extensively in the analysis of digital culture. We begin by updating Berlant’s descriptions of how we think about the contemporary culture of ‘crises’ (2011), drawing on recent documentations to illustrate the interconnected phenomena of “epidemics of loneliness” and isolation in the face of uncertainties of the historical present. To address those gaps, we then explore how cruel optimism and intimate publics have been taken up in studies of digital and social media. We will conclude by addressing how these concepts, as well as Berlant’s most recent work on the inconvenience of others, can best be engaged to help navigate and theorize digital culture. Finally, we take up their 2022 work to explore the crises of polarization as a manifestation of loneliness, through the lens of inconvenience. In conclusion, we will suggest how Berlant’s concepts provide valuable insight for further studies of digital culture.